Auto/biography in Canada : critical directions - Rak, Julie, 1966- (Waterloo, Ont. : Wilfrid Laurier University Press, 2005)
"Auto/biography in Canada: Critical Directions widens the field of auto/biography studies with its sophisticated multidisciplinary perspectives on the theory, criticism, and practice of self, community, and representation. Rather than considering autobiography and biography as discrete genres with definable properties, and rather than focusing on critical approaches, the essays explore auto/biography as a discourse about identity and representation in the context of numerous disciplinary shifts. Auto/biography in Canada looks at how life narratives are made in Canada." "Originating from literary studies, history, and social work, the essays in this collection cover topics that range from queer Canadian autobiography, autobiography and autism, and newspaper death notices as biography to Canadian autobiography and the Holocaust, Grey Owl and authenticity, France Theoret and autofiction, and a new reading of Stolen Life, the collaborative text by Yvonne Johnson and Rudy Wiebe." "Julie Rak's useful "big picture" introduction traces the history of auto/biography studies in Canada. While the contributors chart disciplinary shifts taking place in auto/biography studies, their essays are also part of the ongoing scholarship that is remaking ways to understand Canada."--Jacket
Introduction, widening the field : auto/biography theory and criticism in Canada / Julie Rak -- Generations of the Holocaust in Canadian auto/biography / Susanna Egan & Gabriele Helms -- The modern Hiawatha : Grey Owl's construction of his Aboriginal self / Albert Braz -- "This is my memory, a fact" : the many mediations of Mothertalk: life stories of Mary Kiyoshi Kiyooka / Sally Chivers -- Auto/biographical jurisdictions : collaboration, self-representation, and the law in Stolen life: the journey of a Cree woman / Deena Rymhs -- Biographical versus biological lives : auto/biography and non-speaking persons labelled intellectually disabled / Ann Fudge Schormans -- A transfer boy : about himself / Ljiljana Vuletic & Michel Ferrari -- Creativity, cultural studies, and potentially fun ways to design and produce autobiographical material from subalterns' locations / Si Transken -- Camp, kitsch, queer : Carole Pope and Toller Cranston perform on the page / Andrew Lesk -- Writing lives in death : Canadian death notices as auto/biography / Laurie McNeill -- (Un)tying the knot of patriarchy : agency and subjectivity in the autobiographical writings of France Théoret and Nelly Arcan / Barbara Havercroft -- Auto/bio/fiction in migrant women's writings in Québec : Régine Robin's La Québécoite and L'immense fatigue des pierres / Yuko Yamade -- "The ensign of the mop and the dustbin" : the maternal and the material in autobiographical writings by Laura Goodman Salverson and Nellie McClung / Wendy Roy.
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Autobiography; Biography as a literary form; Canada -- Biography -- History and criticism; Biography; Autobiographies as Topic; Biographies as Topic; Autobiographie; Biographie (Genre littéraire); Canada -- Biographies -- Histoire et critique; Biographies; autobiography (genre); biographies (literary genre); biography (general genre); BIOGRAPHY & AUTOBIOGRAPHY -- Reference; Autobiography; Biography; Biography as a literary form; Canada; Criticism, interpretation, etc